Patterns of Cocaine Use During Treatment: Associations With Baseline Characteristics and Follow-Up Functioning - Roos, Corey R. (J Stud Alcohol Drugs, 2019)
OBJECTIVE: Abstinence outcomes are typically prioritized in the treatment of cocaine use disorder while ignoring patterns of low-frequency cocaine use. This study examined patterns of cocaine use frequency during treatment and evaluated how these patterns related to baseline characteristics and functioning outcomes 6 and 12 months after treatment. METHOD: We used a pooled dataset (N = 720) from seven randomized clinical trials for cocaine use disorder. The Addiction Severity Index (ASI) was used to assess functioning. Repeated-measures latent class analysis was used to derive patterns of cocaine use. RESULTS: Three patterns were identified: abstinence (10.6%), low-frequency use (approximately 1 day/week; 66.3%), and persistent frequent use (approximately 4 days/week; 23.1%). The low-frequency group was associated with male gender, younger age, and a criminal justice referral. The abstinent group had the highest alcohol problem severity score at baseline. At Month 6, the low-frequency group reported lower problem severity than the persistent frequent use group across multiple ASI areas, including the cocaine use as well as psychological, family, employment, and legal domains. At Month 12, the low-frequency group did not differ from the abstinent group in problem severity on any ASI domain and, relative to the persistent frequent use group, had lower cocaine use and employment problem severity. CONCLUSIONS: These findings highlight the importance of adopting a harm reduction approach and recognizing the potential clinical benefits associated with nonabstinent outcomes.